Strigolactones and Cytokinin Interaction in Buds in the Control of Rice Tillering - Zha, Manrong; Zhao, Yanhui; Wang, Yan; Chen, Bingxian; Tan, Zecheng (Frontiers in Plant Science, 2022)
Shoot branching is among the most crucial morphological traits in rice (Oryza sativa L.) and is physiologically modulated by auxins, cytokinins (CKs), and strigolactones (SLs) cumulatively in rice. A number of studies focused on the interplay of these three hormones in regulating rice tiller extension. The present study primarily aimed at determining the impact of different treatments, which were used to regulate rice tiller and axillary bud development on node 2 at the tillering stage and full heading stage, respectively. Transcription levels of several genes were quantified through qRT-PCR analysis, and an endogenous auxin and four types of CKs were determined through LC-MS/MS. Both nutrient deficiency and exogenous SL supply were found to inhibit rice tiller outgrowth by reducing the CK content in the tiller buds. Furthermore, supplying the inhibitor of both exogenous SLs and endogenous SL synthesis could also affect the expression level of OsCKX genes but not the OsIPT genes. Comparison of OsCKX gene expression pattern under exogenous SL and CK supply suggested that the induction of OsCKX expression was most likely via a CK-induced independent pathway. These results combined with the expression of CK type-A RR genes in bud support a role for SLs in regulating bud outgrowth through the regulation of local CK levels. SL functioned antagonistically with CK in regulating the outgrowth of buds on node 2, by promoting the OsCKX gene expression in buds.